Perbedaan Kepuasan Pasien berdasarkan Sistem Pendaftaran Online dan Langsung di Rumah Sakit YPK Mandiri Jakarta Pusat - Tazkia Ghalliya Salsabilla; Nanda Aula Rumana; Dina Sonia; Muniroh, Muniroh (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Patient satisfaction is a level of feeling of a patient that arises as a result of the health service performance results obtained by the patient after comparing with what is felt. Online registration is a registration process that has the function of being able to serve patients online using a particular website or application. Direct registration is an initial process of service that is carried out at the place of registration at a hospital or health facility and meets in person by officers. Satisfaction can occur because of differences in registration systems. The research method used is inferential analysis with a quantitative approach and the chi square test using the SPSS application. The results of the characteristics of the respondents in this study were young respondents, female, S1/D4 education, private employees, and an average income of > Rp.4,901,798. Online registrants amounted to 91 or 74.4%, and on-line registrants amounted to 101 or 52.6%. In the online registration system, 80 or 87.90% of patients were satisfied and 11 or 12.10% dissatisfied. At direct registration, 73 or 72.30% of patients were satisfied and 28 or 27.70% dissatisfied. The number of patient satisfaction based on the online and direct registration system, namely satisfied as many as 153 or 79.7% of patients were dissatisfied 39 or 20.3%. From the results of the chi square test, the result was p = 0.007, which means that there are differences in patient satisfaction based on the online and direct registration systems. In addition, the results obtained were 0R = 2.79, which means that online registration patients are 2.79 times more satisfied than direct registration patients.